Determinación y nomenclatura de las distintas clases de suelos según su contextura - Saiz del Rio, J. F. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A comparison is made between triangular and rectangular coordinates for determining soil classes and the use of rectangular cartesian coordinates is suggested, because of its simplicity. It is proposed, tentatively, the Spanish name of eleven soil classes according to their texture and it is suggested to specify, when publishing soil analysis data, which is the adopted scale, if the international one is not used.